Radio Frequency Interference Detection and Mitigation Algorithms Based on Spectrogram Analysis - Jose Miguel Tarongi; Adriano Camps (Algorithms, 2011)
Radio Frequency Interference (RFI) detection and mitigation algorithms based on a signal’s spectrogram (frequency and time domain representation) are presented. The radiometric signal’s spectrogram is treated as an image, and therefore image processing techniques are applied to detect and mitigate RFI by two-dimensional filtering. A series of Monte-Carlo simulations have been performed to evaluate the performance of a simple thresholding algorithm and a modified two-dimensional Wiener filter.